The Alkerán infusion in the treatment of malignant melanomas of the extremities - Priario, Julio C; Gardiol, Valdo; de los Santos, Julio C; D'Auria, Agustín E; Fiandra, Orestes; Guiguens, Marcos; Guicheff, Vladimir (Cirugía del Uruguay, 2020)
A method for the treatment of malignant melanomas of the extremities is shown: the perfusion with Alkeran with extracorporeal circulation of the isolated limb. The technique used in 16 perfusions performed on 14 patients is described, 8 of the patients remain without evidence of cancerous disease at the present time. Pathological studies performed on tumors excised after the perfusion revealed decreasing in size dissecation and wrinkling of tumors and 'tendency to healing. Microscopical findings were atrophy, necrosis, cellular lisis and liberation of pigment that was phagocited by macrophages. The drug action was larger on pigmented tumor than on amelanic ones. Complications of the procedure were slight or moderate: fibrinolisis, hematuria, infected hematoma and brachial paralysis. The more constant one was slight edema. There was no mortality with this procedure. We believe it is feasible with this procedure to act upon the tumor, the metastases and circulating cells, avoiding in that way mutilating surgery on the affected limb.